Ethnic-Specific Sociodemographic Factors as Determinants of Cognitive Performance: Cross-Sectional Analysis of the Malaysian Elders Longitudinal Research Study - Nur Fazidah Asmuje; Sumaiyah Mat; Phyo Kyaw Myint; Maw Pin Tan (Karger, 2024)
Indexed by SCOPUS/ERA